Gratitude Interventions: Can They Improve Job Satisfaction - Anggono, Tri; Agus Setyawati, Farida; Idongesit Peters, Moses (Green Publisher Indonesia, 2024)
Job satisfaction tends to be low among civil servants at the Sanggau Regency Personnel and Human Resources Development Agency, indicating the need for effective psychological intervention. One form of intervention carried out is gratitude training. This research aims to determine the effectiveness of gratitude training in increasing job satisfaction for civil servants in the BKPSDM Sanggau Regency. The type of research is experimental with the design used is pretest and posttest control group design. The research was conducted on civil servants at the Sanggau Regency Personnel and Human Resources Development Agency with 35 subjects. Data was obtained by filling in the job satisfaction scale before and after gratitude training. The data analysis technique uses the N-Gain Score. The results of the hypothesis test show that there is a significant difference in the level of job satisfaction before and after gratitude training. The average job satisfaction score before training is 119.3, while after training, it increased to 162.5. By using the difference index (N Gain Score), an increase of 70.5064% is recorded. These findings indicate that gratitude training is effective in increasing civil servant job satisfaction in BKPSDM Sanggau Regency.